Analisis Komponen Makna pada Payung Geulis, Kelom Geulis dan Gamparani Sebagai Kerajinan Khas Tasikmalaya - Milla Amellia; Arya Fatahillah; Irenne Edelwis Rondonuwu; Aveny Septi Astriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research contains an analysis of the components of meaning in typical Tasikmalaya crafts, namely payung geulis, kelom geulis and gamparani. The method used in this research is a qualitative method, which is carried out by describing or describing the reality of the facts contained in the research object. The aim of this research is to clarify the differentiating components of the equivalent or lexicon of payung geulis, kelom geulis and gamparani in Indonesian. The analysis technique in this research uses qualitative descriptive techniques, with data collection techniques using reading, listening, note-taking techniques, apart from that, this research also uses semantic analysis. The objects of this research are payung geulis, kelom geulis and gamparani. Based on the meaning component analysis that we have carried out, we can conclude that there are five lexicons related to the payung geulis. The difference lies in the raw materials for making it, the function of use, and even the shape of the type of umbrella. Apart from that, there are also eight lexicons related to the kelom geulis and gamparani. The difference lies in who the user is, the material it is made from, and the situation of the user.